2005
DOI: 10.3201/eid1112.050501
|View full text |Cite
|
Sign up to set email alerts
|

Person-to-Person Transmission of Andes Virus

Abstract: Epidemiologic and genetic data show that person-to-person spread likely took place during the prodromal phase or shortly after it ended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
188
0
12

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(201 citation statements)
references
References 19 publications
1
188
0
12
Order By: Relevance
“…Interpersonal transmission of hantavirus has been reported only in Argentina and Chile, but further investigation indicated that this possibility is very unlikely [4][5][6] . The contact with hantavirus in and of itself does not cause HPS, since infection is dependent on the quantity of viral particles, such that lower concentrations of particles could lead to subclinical infection.…”
Section: Introductionmentioning
confidence: 99%
“…Interpersonal transmission of hantavirus has been reported only in Argentina and Chile, but further investigation indicated that this possibility is very unlikely [4][5][6] . The contact with hantavirus in and of itself does not cause HPS, since infection is dependent on the quantity of viral particles, such that lower concentrations of particles could lead to subclinical infection.…”
Section: Introductionmentioning
confidence: 99%
“…However, ANDV is the only hantavirus in which person-to-person transmission, primarily in small clusters among sex partners and other close household contacts, also occurs. [6][7][8] The annual incidence of HCPS in Chile ranges from 0.2-0.5/ 100.000 inhabitants. Seventy percent of cases occur in men, and the median age is 32 with a range of 6 weeks to 80 y.…”
Section: Introductionmentioning
confidence: 99%
“…c) el manejo del shock con infusión cautelosa de líquidos e inicio precoz de las catecolaminas (42,43); d) el manejo del shock cardiogénico severo con oxigenación extracorpórea a través de membrana (ECMO) (44). Algunos autores aconsejan el uso de antibióticos de amplio espectro hasta la exclusión de otras patologías que, como la leptospirosis o la sepsis bacteriana, cursan con cuadros respiratorios similares.…”
Section: Diagnosisunclassified
“…c) shock management with a cautious infusion of fluids and an early star of catecholamines (42,43). D) severe cardiogenic shock management with extracorporeal membrane oxygenation (ECMO) (44).…”
Section: Diagnosismentioning
confidence: 99%